THE EFFECT OF SUBJECTIVE NORMS, ATTITUDE, PERCEIVED RISK, AND PERCEIVED BEHAVIORAL CONTROL OF BEHAVIORAL INTENTION Mt. Bromo TOURISTS IN EAST JAVA PROVINCE (Universitas Dr. Soetomo, 2022)
This study aims to determine the effect of subjective norm, attitude, perceived risk, perceived behavioral control on behavioral intention on Mount Bromo tourists, East Java. The dependent variable used is behavioral intention, while the independent variable used is subjective norm, attitude, perceived risk, perceived behavioral control. The research method used is causal research with multiple linear regression analysis approach. The research sample was 278 tourists from Mount Bromo, East Java. Data collection techniques by distributing online questionnaires. The data analysis technique used validity test, reliability test, multiple linear regression analysis, classical assumption test, and hypothesis testing. The results showed that subjective norms had a positive and supported effect on behavioral intention and perceived behavioral control had a positive and supported effect on behavioral intention, but attitude had no positive effect and was not supported on behavioral intention. In addition, perceived risk had no positive effect and was not supported on behavioral intention.